Pengaruh Pelatihan Dan Kompetensi Terhadap Kinerja Pegawai Pada Kantor Wilayah DJP Jawa Barat III - Fadiah Lailani; Syahrum Agung; Jani Subakti (CV. ITTC INDONESIA, 2024)
The purpose of this study is to find out how Training and Competency affect employee performance at the DGT West Java Regional Office III. In this study, a quantitative method was used with sample determination using the slovin formula which means using random sampling techniques. Data was obtained through a questionnaire with the Likert Scale, a sample of 109 employees of the DGT West Java Regional Office III was obtained. The data analysis techniques used in statistical test analysis are Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis, Hypothesis Test (t), Hypothesis Test (f), and Determination Coefficient Test using the help of the SPSS application program version 26. Based on the results of the tests carried out, it can be concluded that Training and Competency have a significant effect partially or simultaneously on Employee Performance at the DGT West Java III Regional Office.